Heteroleptic Metal Complexes of a Pyrimidinyl Based Schiff Base Ligand Incorporating 2,2′-Bipyridine Moiety: Synthesis, Characterization, and Biological Studies - Festus, Chioma; Okafor, Sunday N.; Ekennia, Anthony C. (Frontiers in Chemistry, 2019)
A sequence of transition metal complexes of Mn(II), Co(II), Ni(II) and Cu(II) incorporating a novel pyrimidinyl based Schiff base ligand, 2-(4,6-dimethylpyrimidin-2-ylamino)naphthalene-1,4-dione (HL) and 2,2’-bipyridine has been synthesized and characterized using elemental, magnetic, conductance, infrared (FT-IR), nuclear magnetic resonance (1H- and 13C-NMR), electronic (UV-Vis), electrospray ionization mass spectrometry (ESI-MS), thermographic analysis (TGA) and molecular docking studies. The acquired results were consistent with the adoption of the chemical formula, [M(X)(L)(Y)]∙nH2O (where M = Mn, Co, Ni, and Cu; L = Schiff base; X = 2,2’-bipy; Y = OAc and n = 0,1) for the metallic complexes. HL ligand acts as a bidentate chelator and coordinates to metallic ion centre through carbonyl oxygen atom and deprotonated imide nitrogen. Similarly, 2,2’-bipy acts as a non-ionic bidentate chelator coordinating to metallic ion centre via two nitrogen atoms. The mixed ligand complexes were appraised against pathogenic strains: S. aureus, P. aeruginosa, E. coli, B. cereus, P. mirabilis, K. oxytoca, A. niger, A. flevus and R. Stolonifer. The antimicrobial studies gave moderate-good activity. Molecular docking studies on these compounds were done to indicate binding interactions between the compounds and adopted drug targets. Additionally, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of the compounds were determined at different concentrations. The antioxidant study showed good radical scavenging abilities